Media construction of gaffe: a discursive approach - Costa, Julia Lourenço (2019)
In this work we propose to discursively analyze the asseveration (Maingueneau, 2010) of the statement I have conviction of what women do for the house, highlighted by the Brazilian media of the pronouncement of President Michel Temer on International Women’s Day in 2017. The media not only overcomes this statement, as well as classifies it as gaffe (Le Bart, 2003) in its titles and headlines. Based on the analyzes undertaken, it is possible to verify that the controversy (Amossy, 2017) generated by such positioning about the role of women in Brazilian society is minimized as it is scenographed (Maingueneau, 2009) as a gaffe.